Self-care behaviors of village health volunteers in the prevention of coronavirus disease 2019, Banphaeo District, Samut Sakhon Province - Nuannuaeng, Werapong (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This study aims to: 1) to investigate the level of self-care behavior, 2) to explore the association between personal characteristics, knowledge, and social support factors, with a specific focus on self-care behavior, and 3) to examine the challenges, barriers, and recommendations related to self-care among village health volunteers in the prevention of the novel coronavirus disease 2019. The sample group consisted of 274 Village health volunteers from Banphaeo District, Samut Sakhon Province, selected through a rigorous multi-stage random sampling. To gather data, a questionnaire with a reliability range of 0.77-0.93 was employed as the primary data collection instrument. The collected data underwent a comprehensive analysis involving descriptive statistics, correlation analysis, and content analysis. Findings indicate that 1) the majority of the sample demonstrated a high level of self-care behavior overall, except for compliance with registration requirements when entering or exiting public premises, which was moderate. 2) Several factors exhibited significant relationships with self-care behavior, including training on COVID-19 knowledge (rpb= 0.73), prior experience with infectious COVID-19 (rpb= 0.36), knowledge about COVID-19 (rxy= 0.74), emotional support (rxy= 0.70), evaluation support (rxy= 0.71), information support (rxy= 0.71), and material or service support(rxy= 0.71). 3) Identified obstacles to self-care included inconsistent mask usage, prolonged mask reuse, inadequate hand hygiene, and insufficient adherence to social distancing. Recommendations for improvement include emphasizing thorough hand washing, implementing strict control and inspection measures for mask and detection kit distribution, developing an efficient check-in and check-out application system, and launching a public relations campaign to promote continuous compliance with disease prevention measures.